2007
DOI: 10.1007/s10295-007-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal silver ion delivery into hydrophobic coatings with surfactants

Abstract: A much studied oil-soluble surfactant, bis[2-ethylhexyl]sulfosuccinate, sodium salt, was ion exchanged into the silver ion form and dissolved into microemulsions of immiscible polyurethane step monomers. Coating and curing of these microemulsions produced polyurethane coatings that exhibit bactericidal activity against representative Gram negative bacteria. After 24 h exposure, 0.006-0.012% weight Ag relative to coating weight (0.0013-0.0025 micromol Ag/cm2) results in the three-log reduction in Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Tresse et al [32] demonstrated how the effect of tobramycin against planktonic E. coli might be improved by 2,6-dichlorophenol 4-indophenol (DCIP), but that it was not able to increase the effect of the antibiotic against the biofilm, probably due to the inability of DCIP to facilitate the entry of tobramycin through the EPS. Texter et al [33] reported that synthetic surfactants, owing to their amphiphilic nature, are able to deliver silver ion into the EPS to increase the effect of the ion against the biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Tresse et al [32] demonstrated how the effect of tobramycin against planktonic E. coli might be improved by 2,6-dichlorophenol 4-indophenol (DCIP), but that it was not able to increase the effect of the antibiotic against the biofilm, probably due to the inability of DCIP to facilitate the entry of tobramycin through the EPS. Texter et al [33] reported that synthetic surfactants, owing to their amphiphilic nature, are able to deliver silver ion into the EPS to increase the effect of the ion against the biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Sol-gel processing [68,84,[290][291][292][293], loading nano-particles into liposomes [233,243], using nanoporous structure of cellulose fiber as a nano-reactor for in situ synthesis of metal nano-particles [99], sputtering of nano-particles during plasma polymerization [294], adding ion exchange functionalized surfactants in polymerization process [295] and conventional pad-dry-cure system (process) for the treatment of fabric with nano-sized colloidal particles [296] are among other used methods for the modification of polymeric substrates.…”
Section: Textile Modification Methodsmentioning
confidence: 99%
“…Although the mechanism of action still remains disputed, it is generally accepted that free silver ions (FSI), present or leaking from the materials in contact with the food matrix, are able to bind to membrane constituents, destabilizing the membrane potential and causing proton leakage (Liau et al, 1997;Matsumura et al, 2003). They also interfere with DNA replication and ion transport across the respiratory chain (Feng et al, 2000;Semeykina and Skulachev, 1990;Texter et al, 2007), all of which eventually lead to cell death. Due to this combination of unspecific mechanisms, silver ions are not likely to develop any resistances and are active against a very broad spectrum of bacteria, yeasts, fungi and even viruses in tiny concentrations, remaining nontoxic to human cells (Russell and Hugo, 1994).…”
Section: Introductionmentioning
confidence: 99%